Model Pengembangan Agrowisata Berbasis Kopi Sebagai Daya Tarik Wisata Desa Wisata Colo Kudus - Mahadika Pradipta Himawan; Haniek Listyorini; Trenggono Trenggono; Dyan Triana Putra; Julian Andriani Putri (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2023)
This research was conducted in the Colo Kudus Tourism Village, Central Java, which aims to understand and analyze the coffee-based agro-tourism development model as a tourist attraction in the Colo Kudus Tourism Village. And analyze what obstacles are experienced by the Colo Kudus Tourism Village Agrotourism. The data of this study were obtained through observation and interviews, the informants used in the study were 5 respondents. The results of the study are expected to provide useful information for coffee activists, the Colo Coffee community. The data obtained were processed using descriptive qualitative. Qualitative analysis uses data analysis, namely data collection, data reduction, data presentation, and drawing conclusions. The results showed that Arowisata Colo Tourism Village has a strategy model such as Coffee Education Tourism, training for farmers.